På jakt efter dalanavellaven Umbilicaria subglabra samt klättringens påverkan på lav- och mossvegetationen på Ålandsklipporna utanför Uppsala - Fredriksson, Carl-Johan (2007)
In Sweden Umbilicaria subglabra has its only known occurrence in Lybergsgnupens nature reserve in the county of Dalarna where it has been found only once in 1936. It was found on the east-facing rock spur, approximately 650 meters above sea-level. The lichen is now red-listed as Regionally Extinct (RE) in Sweden. The aim of this study was find U. subglabra. I have with the aid of climbing equipment done a thoroughly investigation of the cliff-face at Lybergsgnupen. My conclusion is that U. subglabra no longer grows on the location. The cliff harbours eleven other species belonging to the genus Umbilicaria. Their population sizes were assessed. Three other locations in the area were also searched for the presence of U. subglabra with negative results.